Itraconazole as a successful treatment to manage Batrachochytrium dendrobatidis outbreaks in ex-situ frog colonies in Argentina: dose and schedule for Pleuroderma somuncurense - Arellano, María Luz (2024)
The article discusses the successful use of Itraconazole to manage Batrachochytrium dendrobatidis outbreaks in ex-situ frog colonies in Argentina, focusing on the El Rincon Stream Frog, a Critically Endangered species. The study details the treatment protocol, including dose and schedule, to combat the chytrid fungus infection that caused mass mortality events in the frog colony. The research highlights the importance of preemptive biosecurity measures and the need for further experiments to determine the most effective treatment for endangered amphibian species in ex-situ settings.